TURKEY’S FIRST ORGANIC BAZAAR - Demir, A. Yonca (European Scientific Journal, ESJ, 2013)
This paper explores the workings of a national open air marketplace solely for certified organic products. We use net sales and participation data collected at the marketplace, unstructured interviews with farmers and consumers, and participant observation. The sales figures display seasonality and suggest an expansion in the domestic organic sector after the entry of the organic bazaar to the lives of Istanbul’s inhabitants. We compare the organic bazaar to the conventional fresh produce market in terms of food safety and quality, price, wholesale market feature, transactional proximity and the effectiveness of transportation systems used in each setting. We point out similarities to and differences from countries with large developed organic markets and make policy suggestions. We also highlight possible research questions arising from the network of farmers, processors, warehouses and retailers, we provide the design of further research.